Examining the Values of Character Education Based on Local Wisdom in the Baseloa Tradition in the Sungai Liuk Community - Pitri, Nandia; Meirisa, Silvia (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
Sungai Liuk is an area that has various traditions, one of which is baseloa. Baseloa is a tradition carried out when one of its community members wants to make a house foundation, this tradition is still carried out by the people of Sungai Liuk until now. This research aims to explore what character education values are contained in baseloa activities in the Sungai Liuk community; in addition, it is also to see how the development of this tradition so that it can be preserved until now which will later become a character or moral for the local community of Sungai Liuk.The method used in this research is the historical method. The results showed that character education can be formed from the local wisdom of the local community, this is because in the implementation of certain traditions there are special rituals that are usually carried out by the community. So that from this habit, an attitude or behavior is created which will increasingly form a community character. In this case, the baseloa tradition of the Sungai Liuk community contains character education values, namely religious, tolerance, democratic, love for the country, friendly/communicative, and social care that need to be instilled in the nation's next generation.